FOOD RECALL MOBILE APPLICATION DESIGN AS A MEASURING TOOL FOR INDIVIDUAL AND FAMILY FOOD CONSUMPTION - Ni Nengah Asti Kartika Sari; Fajar Irianto; Anisa Tri Hutami (Poltekkes Kemenkes Semarang, 2022)
The information technology development has been used to create SITAMARI (daily food record system) that can be used as an assessment that correlates with a daily intake of food or the eating habit of the society that has been designed to be easy to use, efficient, and precise. The goals of this research were to design the SITAMARI application as the learning media of the Food Consumption Survey practice of the nutrition major's students. For now, the SITAMARI application is still in the development stage and thus hasn’t been launched online for a larger audience. This research used the quasi-experimental design of one group pre-test-post-test. Research subjects are 25 3rd-grade Diploma III Nutrition students, aged 18 – 25 years old, who have already understood 24 hours food recall method, and have a well-working Android smartphone. A pre-test questionnaire was given, followed respectively by the treatment and the same questionnaire as the post-test. Lastly, the Likert questionnaires about their perception after using the application were filled out. The statistical analysis using the paired sample t-test showed that t-calculated t-table with a significant probability value of 0.00 0.05. It was concluded that the use of the application is effective in the students' learning. The user satisfaction survey showed the application was attractive in design and easy to use and increased knowledge in Food Consumption Survey. However, the results of the food recall calculation still need to be validated comparatively with the manual food recall format.